SOSIALISASI PENTINGNYA DIGITAL MARKETING UNTUK PEMASARAN PRODUK UMKM MASYARAKAT DESA KARANG SARI KOTA TANGERANG - Husain, Syepry Maulana; Aksani, Muhammad Lutfhi; Basri, Firdiansyah Firdaus; Saputra, Muhammad Rizka (Universitas Muhammadiyah Tangerang, 2023)
Digital marketing has become a very important aspect of modern marketing. This has changed the way businesses interact with customers and reach their target audience. Advances in technology, especially the internet and mobile devices, have changed the way people interact with information and brands. Easy access to the internet and mobile devices has opened the door to digital marketing. Today's consumers are more likely to search for products and services online, read reviews, and conduct research before making a purchasing decision. This creates opportunities for businesses to leverage digital platforms to reach and influence consumers. Digital marketing allows businesses to use user data to target advertising more precisely. This means advertising can be tailored to individual interests and preferences, making it more effective. One of the advantages of digital marketing is the ability to better measure and analyze campaign results. This allows businesses to understand what is working and what is not, so they can improve their marketing strategies. Many businesses compete for customer attention in the digital world. This drives innovation and continuous improvement in digital marketing practices. Digital marketing is more accessible to small and medium businesses, due to the lower cost of entry compared to traditional advertising. This provides an opportunity for small businesses to compete with big players. Although digital marketing offers many benefits, privacy issues also arise as data collection increases. This has resulted in changes in data privacy regulations, such as the European Union's GDPR. Digital marketing is becoming an important tool for businesses and organizations to grow their online presence, reach a wider audience, and influence consumers in a more measurable way. With a good understanding of trends and developments in digital marketing, people can use it to their advantage in promoting their business or understanding how information is presented to them online.